2010
DOI: 10.1016/j.preteyeres.2010.02.001
|View full text |Cite
|
Sign up to set email alerts
|

Linking structure and function in glaucoma

Abstract: The glaucomas are a group of relatively common optic neuropathies, in which the pathological loss of retinal ganglion cells causes a progressive loss of sight and associated alterations in the retinal nerve fiber layer and optic nerve head. The diagnosis and management of glaucoma are often dependent on methods of clinical testing that either, 1) identify and quantify patterns of functional visual abnormality, or 2) quantify structural abnormality in the retinal nerve fiber layer, both of which are caused by l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
316
4
2

Year Published

2011
2011
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 259 publications
(332 citation statements)
references
References 98 publications
(186 reference statements)
10
316
4
2
Order By: Relevance
“…Similar results have been reported previously [8,30,31]. Our finding of macular GCC loss could be explained by the loss of retinal ganglion cells and axons prior to the thinning of the RNFL [32,33]. In addition, the superior region of the macular is more susceptible to initial diabetic damage than the other regions.…”
Section: Discussionsupporting
confidence: 91%
“…Similar results have been reported previously [8,30,31]. Our finding of macular GCC loss could be explained by the loss of retinal ganglion cells and axons prior to the thinning of the RNFL [32,33]. In addition, the superior region of the macular is more susceptible to initial diabetic damage than the other regions.…”
Section: Discussionsupporting
confidence: 91%
“…2 A complete assessment of rates of disease progression requires both structural and functional measures, as it is known that many patients seem to progress by one method and not the other. [3][4][5][6] Although functional outcomes have an unquestionable relevance to patients, it has been shown that structural changes can often precede functional losses and be an earlier marker of deterioration. More importantly, a recent study showed that structural changes observed on optic disc stereophotographs are predictive of future functional losses and, therefore, carry clinically relevant prognostic information.…”
Section: Introductionmentioning
confidence: 99%
“…Generally speaking, quantitative metrics of visual performance reflect the extent of both injury and protection that can only be inferred by morphologic analyses; moreover, functional alterations are often seen in glaucoma in the absence of gross changes in retinal cell structure [45,46], resulting in nonlinear structure-function relationships [47,48]. In our model, impairments in visual function and performance to levels of about 70-75 % of fellow eye controls, concomitant with optic nerve axon integrity and soma survival on the order of 80-85 % of fellow eye controls, are indicative of mild-tomoderate injury after 3 weeks of sustained IOP elevation.…”
Section: Discussionmentioning
confidence: 99%